Clinical impact of triglyceride deposit cardiomyovasculopathy, coronary atherosclerosis with triglyceride deposition, on vascular failure after drug-eluting stent implantation. (25th November 2020) - Nakano, Y; Onishi, T; Suzuki, M; Niwa, T; Mukai, K; Ando, H; Ohashi, H; Waseda, K; Takashima, H; Amano, T
Abstract: Background: Triglyceride deposit cardiomyovasculopathy (TGCV) is a novel cardiovascular disorder, encoded as orphan disease in Europe in 2019, characterized by excessive accumulation of triglyceride in vascular smooth muscle cells, leading to coronary artery disease (CAD). However, there is no data about impact of TGCV on vascular failure after coronary stent implantation. Purpose: To assess impact of TGCV on the outcome following coronary stent implantation in CAD patients with diabetes mellitus (DM) as Study 1, and chronic hemodialysis as Study 2. Methods: This is multicenter retrospective estimation consisting of two studies. Study 1) Among 526 consecutive patients suspected of having CAD who underwent coronary angiography (CAG) and iodine-123-β-methyliodophenyl-pentadecanoic acid (BMIPP) scintigraphy, a tracer for the diagnosis of TGCV, data from 81 patients with DM were analyzed. The patients were divided into two groups; TGCV (n=7) or non-TGCV (n=74). All patients were implanted with a second-generation DES and underwent follow-up CAG. Binary restenosis (ISR), defined as angiographic luminal diameter >50% by quantitative coronary angiography, in-stent late loss were assessed in 15 stents of TGCV patients and 111 stents of non-TGCV patients. Study 2) Similarly, among 88 chronic hemodialysis patients, ISR and in-stent late loss were assessed in 12 stents of 9 TGCV patients and 21 stents of 17 non-TGCV patients. Results: Study 1) There were no significant differences in baseline characteristics between the two groups. In-stent late loss was greater in TGCV group than in non-TGCV group (0.91mm [0.27, 2.39] vs. 0.15mm [0.03, 0.35]; p<0.001), resulting in greater incidence of ISR in TGCV group than in non-TGCV group (46.7% vs. 9.0%; p<0.001). Multivariable logistic analysis revealed TGCV to be an independent predictor for vascular failure after DES implantation in patients with DM. Study 2) Similarly, in-stent late loss and incidence of ISR were greater in TGCV group than in non-TGCV group (1.20±0.99mm vs. 0.50±0.70, p=0.02; 58.3% vs. 9.5%, p=0.002, respectively). TGCV was an independent predictor for vascular failure after DES implantation in chronic hemodialysis patients. Conclusion: Apart from existing risk factors such as DM and hemodialysis, TGCV could contribute to a novel risk factor for vascular failure, even in the second-generation DES era. Funding Acknowledgement: Type of funding source: None